2003
DOI: 10.1007/s00520-002-0355-2
|View full text |Cite
|
Sign up to set email alerts
|

Curative and palliative aspects of regional chemotherapy in combination with surgery

Abstract: Many attempts have been made in the last two decades to improve the outcome of patients with advanced or metastasised solid tumours. In particular, combined-modality treatment strategies combining surgery with more localised therapies, e.g. radiotherapy, or systemic therapies such as chemotherapy have yielded promising data. The aim of regional chemotherapy is to improve locoregional cytostatic drug concentrations by achieving greater local efficacy and to diminish systemic side effects by reducing plasma drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Bei der ILP konnte die lokale Injektion von Chemotherapeutika in die Lunge zusammen mit der lokalen Hyperthermie eine verbesserte Absorption und eine erhöhte zytotoxische Wirkung der applizierten Medikamente schaffen [15]. Muller et al berichteten, dass die Konzentration der Chemotherapeutika an der Tumorstelle doppelt so hoch ist wie bei einer systemischen Chemotherapie [16]. Zahlreiche Tierstudien konnten diese vielversprechenden Ergebnisse bestätigen [17], jedoch konnte sich die ILP klinisch nicht etablieren, da sie nicht reproduzierbar ist.…”
Section: Isolierte Lungenperfusion (Ilp)unclassified
See 1 more Smart Citation
“…Bei der ILP konnte die lokale Injektion von Chemotherapeutika in die Lunge zusammen mit der lokalen Hyperthermie eine verbesserte Absorption und eine erhöhte zytotoxische Wirkung der applizierten Medikamente schaffen [15]. Muller et al berichteten, dass die Konzentration der Chemotherapeutika an der Tumorstelle doppelt so hoch ist wie bei einer systemischen Chemotherapie [16]. Zahlreiche Tierstudien konnten diese vielversprechenden Ergebnisse bestätigen [17], jedoch konnte sich die ILP klinisch nicht etablieren, da sie nicht reproduzierbar ist.…”
Section: Isolierte Lungenperfusion (Ilp)unclassified
“…In ILP, the local injection of chemotherapeutics into the lung together with local hyperthermia was able to improve absorption and increase the cytotoxic effect of the applied medications [15]. Muller et al reported that the concentration of chemotherapeutics at the tumor site is double the amount in systemic chemotherapy [16]. Numerous animal studies were able to confirm these promising results [17].…”
Section: Isolated Lung Perfusion (Ilp)mentioning
confidence: 99%
“…HCC receives a majority of their blood supply from the hepatic artery compared to the portal vein for normal liver. In TACE, a catheter is placed in the branches of the hepatic artery and chemotherapy agents can be infused into the artery [105]. Drug eluting beads (DEB) is often used in combination with TACE to deliver chemotherapy into adjacent tissue [106,107].…”
Section: Local Implantationmentioning
confidence: 99%
“…25,26 With isolated lung perfusion, it is possible to obtain drug concentrations near the tumor site twice as high as those achieved with systemic chemotherapy with only 25% of the systemic dose. 27 Several recent animal studies have reconfirmed that tumor drug concentrations and therapeutic efficacy are significantly higher 28,29 with isolated lung perfusion than with systemic chemotherapy.…”
Section: Isolated Lung Perfusionmentioning
confidence: 99%